Copolymer, preparation method thereof and fracturing fluid
By developing a shear thickening copolymer, the problem of the existing fracturing fluid reducing viscosity at high temperatures is solved, and high viscosity maintenance is achieved under 200°C, which is suitable for deep well reservoir transformation.
Patent Information
- Application Number
- CN202311338847.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-10-16
AI Technical Summary
The viscosity of the existing fracturing fluid decreases under high temperature conditions, weakens the ability to carry sand, resulting in complex situations such as sand decomposition. In addition, the molecular fracture of the traditional guar gum fracturing fluid at high temperatures, affecting the transformation effect.
A shear thickening copolymer is developed with a structure including a copolymer of specific monomers, which increases viscosity by introducing mechanical force-responsive groups into the polymer, forming more stable covalent bonds under shearing.
The copolymer was sheared at 200°C and 100s-1 for 120 minutes, and the viscosity was maintained above 100mPa·s, which significantly improved the high temperature resistance of the fracturing fluid and was suitable for deep well reservoir transformation.
Smart Images

Figure CN119842026A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fracturing fluids, and in particular to a copolymer and a preparation method thereof and a fracturing fluid, and more particularly to a shear thickening copolymer for high temperature resistant fracturing fluids and a preparation method thereof and a high temperature resistant fracturing fluid containing the shear thickening copolymer. Background Art
[0002] With the continuous deepening of oil and gas exploration and development, the proportion of deep oil and gas resources has gradually increased. Reservoir transformation is currently one of the most effective ways to increase the productivity of oil and gas wells. However, deep well reservoir transformation faces many difficulties. One of the important problems is the insufficient temperature resistance of fracturing fluid. With the increase of reservoir depth, the temperature gradually increases. The temperature of some reservoirs has reached or exceeded 200°C. High temperature often causes the viscoelasticity of fracturing fluid to decrease sharply, and the sand carrying capacity is weakened, resulting in complex situations such as sand stripping. In addition, the performance of fracturing fluid will also decrease under long-term shearing, making it difficult for the existing fracturing fluid system to effectively adapt to construction needs. Although the traditional guar gum fracturing fluid has a good thickening effect, the glycosidic bond on the main chain of the guar gum molecule will break at 177°C, which seriously restricts its application in high-temperature resistant fracturing fluid, and the residue after gel breaking will damage the formation and affect the fracturing transformation effect. The synthetic polymer fracturing fluid system does not contain water-insoluble substances. The main chain of the polymer is a carbon-carbon single bond, which has excellent thermal stability. Therefore, as the demand for high-temperature resistant fracturing fluids in oilfield operations increases, it is necessary to develop a high-temperature resistant polymer fracturing fluid system with a temperature resistance of up to 200°C for fracturing and production increase in low-permeability and high-temperature wells. Summary of the invention
[0003] The purpose of the present invention is to overcome the problem of insufficient temperature resistance of fracturing fluid in the prior art, and to provide a shear thickening copolymer for high temperature resistant fracturing fluid and a preparation method thereof, and a high temperature resistant fracturing fluid containing the shear thickening copolymer. The fracturing fluid containing the shear thickening copolymer of the present invention has excellent high temperature resistance.
[0004] In order to achieve the above object, the present invention provides a copolymer, wherein the copolymer has a structure shown in formula (1),
[0005]
[0006] In formula (1), R1 and R2 are each independently selected from halogen;
[0007] R3 and R4 are each independently selected from H and an alkyl group having 1 to 6 carbon atoms;
[0008] R5 is selected from an alkyl group having 1 to 20 carbon atoms;
[0009] a, b, c and d represent the molar percentage of the structural unit, a is 55-75%, b is 15-25%, c is 1-10%, and d is 0.1-5%;
[0010] n is an integer selected from 5-10.
[0011] Preferably, in formula (1), R1 and R2 are each independently selected from F, Cl, Br or I, preferably each independently selected from Cl or Br;
[0012] R3 and R4 are each independently selected from H and an alkyl group having 1 to 3 carbon atoms, preferably each independently selected from H and a methyl group;
[0013] R5 is selected from an alkyl group having 6 to 10 carbon atoms, preferably an octyl group;
[0014] a, b, c and d represent the molar percentage of the structural unit, a is 70-75%, b is 15-25%, c is 4-9%, and d is 0.5-2%;
[0015] n is selected from 5, 7, 9 or 10.
[0016] Preferably, the copolymer has a structure shown in formula (2),
[0017]
[0018] In formula (2), a, b, c and d represent the molar percentage of the structural unit, a is 55-75%, b is 15-25%, c is 1-10%, and d is 0.1-5%;
[0019] n is an integer selected from 5-10.
[0020] Preferably, in formula (2), a, b, c and d represent the molar percentage of the structural unit, a is 70-75%, b is 15-25%, c is 4-9%, and d is 0.5-2%;
[0021] n is selected from 5, 7, 9 or 10.
[0022] According to a second aspect of the present invention, a method for preparing a copolymer is provided, wherein the method comprises the following steps:
[0023] 1) in the presence of an initiator, subjecting a monomer solution containing monomer A, monomer B, monomer C and monomer D to a polymerization reaction to obtain a polymer intermediate;
[0024] 2) a step of subjecting the polymer intermediate to a halogenation reaction with a halogenating agent,
[0025] Wherein, the monomer A is acrylamide and / or alkyl acrylamide, the monomer B is acrylic acid and / or alkyl acrylic acid, the monomer C is sorbic acid, methyl sorbate or ethyl sorbate, and the monomer D is alkylphenol polyoxyethylene ether methacrylate;
[0026] The alkyl groups in the alkyl acrylamide and the alkyl acrylic acid are independently selected from H and alkyl groups with 1 to 6 carbon atoms; the alkyl group in the alkylphenol polyoxyethylene ether methacrylate is selected from alkyl groups with 1 to 20 carbon atoms;
[0027] Based on the total molar amount of monomer A, monomer B, monomer C and monomer D, the monomer A is 55-75 mol%, the monomer B is 15-25 mol%, the monomer C is 1-10 mol%, and the monomer D is 0.1-5 mol%.
[0028] Preferably, the alkyl groups in the alkyl acrylamide and the alkyl acrylic acid are each independently selected from H and an alkyl group having 1 to 3 carbon atoms, preferably H and methyl.
[0029] Preferably, the alkyl group in the alkylphenol polyoxyethylene ether methacrylate is selected from alkyl groups having 6 to 10 carbon atoms, preferably octyl.
[0030] Preferably, based on the total molar amount of monomer A, monomer B, monomer C and monomer D, the monomer A is 70-75 mol%, the monomer B is 15-25 mol%, the monomer C is 4-9 mol%, and the monomer D is 0.5-2 mol%.
[0031] Preferably, the monomer A is one or more of acrylamide, methacrylamide, ethyl acrylamide and propyl acrylamide.
[0032] Preferably, the monomer B is one or more of acrylic acid, methacrylic acid, ethacrylic acid and propylacrylic acid;
[0033] Preferably, the monomer D is one or more of octylphenol polyoxyethylene ether methacrylate (n=5 in the following formula (3)), octylphenol polyoxyethylene ether methacrylate (n=7 in the following formula (3)), octylphenol polyoxyethylene ether methacrylate (n=9 in the following formula (3)) and octylphenol polyoxyethylene ether methacrylate (n=10 in the following formula (3)).
[0034]
[0035] Preferably, the initiator is one or more of azobisisobutyronitrile, azobisisovaleronitrile and azobisisobutyramidine hydrochloride.
[0036] Preferably, the amount of the initiator is 0.05-0.2% of the total weight of the monomers.
[0037] Preferably, the solvent in the monomer solution is one or more of methanol, ethanol, diethyl ether, acetone, toluene and xylene, preferably one or more of ethanol, diethyl ether and acetone.
[0038] Preferably, the polymerization reaction conditions include: polymerization temperature of 60-70° C., and polymerization time of 7-8 hours.
[0039] Preferably, in step 2), the halogenating agent is bromoform.
[0040] Preferably, the amount of the halogenating agent used is 3-8% by weight of the polymer intermediate.
[0041] Preferably, the conditions of the halogenation reaction include: reaction temperature of 5-45° C., and reaction time of 10-80 hours.
[0042] According to a third aspect of the present invention, a fracturing fluid is provided, wherein the fracturing fluid contains the copolymer according to the first aspect of the present invention.
[0043] Preferably, the content of the copolymer in the fracturing fluid is 0.1-1 wt %.
[0044] The copolymer of the present invention introduces a mechanical force responsive group. Under shearing, the mechanical force responsive group will open and undergo a nucleophilic substitution reaction to form a more stable covalent bond, thereby increasing the viscosity of the copolymer. As described later, the fracturing fluid system prepared with the shear thickening copolymer is heated to 200°C for 100s. -1 The viscosity of the shear thickening copolymer is kept above 100 mPa·s after shearing for 120 minutes under the above conditions. In addition, the preparation method of the shear thickening copolymer of the present invention is easy to operate, has low raw material cost, and has broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is the infrared spectrum of the shear thickening copolymer obtained in Example 1.
[0046] Figure 2 This is the variable shear rheological curve of the fracturing fluid prepared with 0.3 wt% of the copolymer in Example 1.
[0047] Figure 3 This is the shear recovery rheological curve of the fracturing fluid prepared with 0.3 wt% of the copolymer in Example 2.
[0048] Figure 4 This is the temperature and shear resistance rheological curve of the fracturing fluid prepared with 0.3 wt% of the copolymer in Example 3.
[0049] Figure 5This is the temperature and shear resistance rheological curve of the fracturing fluid prepared with 0.4 wt% of the copolymer in Example 3.
[0050] Figure 6 This is the temperature and shear resistance rheological curve of the fracturing fluid prepared with 0.5% by weight of the copolymer in Example 4.
[0051] Figure 7 This is the temperature and shear resistance rheological curve of the fracturing fluid prepared with 0.6 wt% of the copolymer in Example 5. DETAILED DESCRIPTION
[0052] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0053] In the present invention, "halogen" is F, Cl, Br or I, preferably F, Cl or Br, more preferably Cl or Br, and particularly preferably Br.
[0054] In the present invention, the "alkyl group having 1 to 6 carbon atoms" may be a straight chain alkyl group or a branched chain alkyl group, and examples thereof include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, etc. Among them, methyl, ethyl or n-propyl is preferred, and methyl is particularly preferred.
[0055] In the present invention, the alkyl group having 1 to 20 carbon atoms may be a straight chain alkyl group or a branched chain alkyl group, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, isohexyl, among which octyl is preferred.
[0056] According to a first aspect of the present invention, a copolymer is provided, wherein the copolymer has a structure shown in formula (1):
[0057]
[0058] In formula (1), R1 and R2 are each independently selected from halogen;
[0059] R3 and R4 are each independently selected from H and an alkyl group having 1 to 6 carbon atoms;
[0060] R5 is selected from an alkyl group having 1 to 20 carbon atoms;
[0061] a, b, c and d represent the molar percentage of the structural unit, a is 55-75%, b is 15-25%, c is 1-10%, and d is 0.1-5%;
[0062] n is an integer selected from 5-10.
[0063] In the present invention, although the structure of the copolymer is represented by formula (1), it does not mean that the monomer structures must be connected in the order shown in formula (1). It is a copolymer structure in which the monomer structures are arbitrarily connected to each other.
[0064] The copolymer of the present invention is a shear thickening copolymer. The copolymer of the present invention has excellent shear thickening performance, and the reason is presumably as follows: as shown in the following formula (the reaction chemical equation of the copolymer under shear), dibromocyclopropane opens its ring after being subjected to shear force to generate dibromoallyl groups, which then undergo nucleophilic substitution reaction with the amide groups in acrylamide, so that crosslinking occurs between the copolymers, thereby increasing the viscosity.
[0065]
[0066] According to the present invention, preferably, in formula (1), R1 and R2 are each independently selected from F, Cl, Br or I, more preferably each independently selected from F, Cl or Br, more preferably each independently selected from Cl or Br, and particularly preferably Br.
[0067] According to the present invention, preferably, in formula (1), R3 and R4 are each independently selected from H and an alkyl group having 1 to 3 carbon atoms, preferably each independently selected from H and a methyl group, and particularly preferably H.
[0068] According to the present invention, preferably, R5 is selected from an alkyl group having 6 to 10 carbon atoms, more preferably an octyl group.
[0069] According to the present invention, preferably, a, b, c and d represent the molar percentage of the structural unit, a is 70-75%, b is 15-25%, c is 4-9%, and d is 0.5-2%.
[0070] The above-mentioned a represents the molar percentage of the structural unit, and examples thereof include 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, etc., and the range consisting of any two of the above.
[0071] The above-mentioned b represents the molar percentage of the structural unit, and examples thereof include 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, etc., and the range formed by any two of the above.
[0072] The above-mentioned c represents the molar percentage of the structural unit, and examples thereof include 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., and the range consisting of any two of the above.
[0073] The above-mentioned d represents the molar percentage of the structural unit, and examples thereof include 0.1%, 0.2%, 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, etc., and the range consisting of any two of the above.
[0074] According to the present invention, n is selected from 5, 6, 7, 8, 9 or 10; preferably, n is selected from 5, 7, 9 or 10.
[0075] In a preferred embodiment of the present invention, the copolymer has a structure shown in formula (2),
[0076]
[0077] In formula (2), a, b, c and d represent the molar percentage of the structural unit, a is 55-75%, b is 15-25%, c is 1-10%, d is 0.1-5%; n is an integer selected from 5-10.
[0078] Preferably, in formula (2), a, b, c and d represent the molar percentage of the structural unit, a is 70-75%, b is 15-25%, c is 4-9%, d is 0.5-2%; and n is selected from 5, 7, 9 or 10.
[0079] According to a second aspect of the present invention, a method for preparing a copolymer is provided, wherein the method comprises the following steps:
[0080] 1) in the presence of an initiator, subjecting a monomer solution containing monomer A, monomer B, monomer C and monomer D to a polymerization reaction to obtain a polymer intermediate;
[0081] 2) a step of subjecting the polymer intermediate to a halogenation reaction with a halogenating agent,
[0082] Wherein, the monomer A is acrylamide and / or alkyl acrylamide, the monomer B is acrylic acid and / or alkyl acrylic acid, the monomer C is sorbic acid, methyl sorbate or ethyl sorbate, and the monomer D is alkylphenol polyoxyethylene ether methacrylate;
[0083] The alkyl groups in the alkyl acrylamide and the alkyl acrylic acid are independently selected from H and alkyl groups with 1 to 6 carbon atoms; the alkyl group in the alkylphenol polyoxyethylene ether methacrylate is selected from alkyl groups with 1 to 20 carbon atoms;
[0084] Based on the total molar amount of monomer A, monomer B, monomer C and monomer D, the monomer A is 55-75 mol%, the monomer B is 15-25 mol%, the monomer C is 1-10 mol%, and the monomer D is 0.1-5 mol%.
[0085] According to the present invention, preferably, the alkyl groups in the alkyl acrylamide and the alkyl acrylic acid are each independently selected from H and an alkyl group having 1 to 3 carbon atoms, more preferably each independently selected from H and methyl, and particularly preferably H.
[0086] According to the present invention, preferably, the alkyl group in the alkylphenol polyoxyethylene ether methacrylate is selected from alkyl groups having 6 to 10 carbon atoms, more preferably octyl group.
[0087] According to the present invention, preferably, based on the total molar amount of monomer A, monomer B, monomer C and monomer D, the monomer A is 70-75 mol%, the monomer B is 15-25 mol%, the monomer C is 4-9 mol%, and the monomer D is 0.5-2 mol%.
[0088] According to the present invention, preferably, the monomer A is one or more of acrylamide, methacrylamide, ethyl acrylamide and propyl acrylamide; more preferably, the monomer A is acrylamide and / or methacrylamide; particularly preferably, the monomer A is acrylamide.
[0089] According to the present invention, preferably, the monomer B is one or more of acrylic acid, methacrylic acid, ethacrylic acid and propylacrylic acid; more preferably, the monomer B is acrylic acid and / or methacrylic acid; particularly preferably, the monomer B is acrylic acid.
[0090] According to the present invention, preferably, the monomer D is one or more of octylphenol polyoxyethylene ether methacrylate (n=5), octylphenol polyoxyethylene ether methacrylate (n=7), octylphenol polyoxyethylene ether methacrylate (n=9) and octylphenol polyoxyethylene ether methacrylate (n=10). Here, n refers to the number of repeating units of polyoxyethylene ether.
[0091] Particularly preferably, the monomer D is selected from one or more of octylphenol polyoxyethylene ether methacrylate (n=5 in the following formula (3)), octylphenol polyoxyethylene ether methacrylate (n=7 in the following formula (3)), octylphenol polyoxyethylene ether methacrylate (n=9 in the following formula (3)) and octylphenol polyoxyethylene ether methacrylate (n=10 in the following formula (3)).
[0092]
[0093] In the present invention, monomer AD can be obtained commercially or by conventional synthesis methods in the art. For example, monomer D can be obtained by reacting alkylphenol polyoxyethylene ether with methacryloyl chloride.
[0094] According to the present invention, preferably, the initiator is an azo initiator; more preferably, the initiator is one or more of azobisisobutyronitrile, azobisisovaleronitrile and azobisisobutyramidine hydrochloride.
[0095] Preferably, the amount of the initiator is 0.05-0.2% by weight of the total weight of the monomers, preferably 0.05-0.1%, particularly preferably 0.1%.
[0096] According to the present invention, the monomer solution is obtained by mixing monomers in a solvent, and the solvent in the monomer solution may be one or more of methanol, ethanol, ether, acetone, toluene and xylene, preferably one or more of ethanol, ether and acetone, and more preferably ethanol.
[0097] According to the present invention, the monomer content in the monomer solution may be 5-15% by weight, preferably 5-10% by weight, and more preferably 8-10% by weight.
[0098] According to the present invention, the polymerization reaction conditions include: polymerization temperature of 50-80°C, polymerization time of 5-15 hours; preferably, the polymerization reaction conditions include: polymerization temperature of 60-70°C, polymerization time of 7-8 hours.
[0099] According to the present invention, in step 2), the halogenating agent is bromoform;
[0100] Preferably, the amount of the halogenating agent used is 3-8% by weight of the polymer intermediate, preferably 4-7%, more preferably 5-6%, and particularly preferably 5%.
[0101] According to the present invention, in step 2), preferably, the halogenation reaction is carried out in the presence of a catalyst (preferably hexadecyltrimethylammonium bromide). The amount of the catalyst used is 0.001-0.1%, preferably 0.005-0.01%, based on the weight of the polymer intermediate.
[0102] According to the present invention, in step 2), the conditions of the halogenation reaction include: reaction temperature of 5-45°C, reaction time of 10-80 hours; preferably, the conditions of the halogenation reaction include: reaction temperature of 20-40°C, reaction time of 15-30 hours.
[0103] According to a third aspect of the present invention, a fracturing fluid is provided, wherein the fracturing fluid contains the copolymer described in the first aspect of the present invention.
[0104] According to the present invention, the content of the copolymer in the fracturing fluid is 0.1-1% by weight, more preferably 0.2-0.8% by weight, and more preferably 0.3-0.6% by weight.
[0105] The present invention will be described in detail below by way of examples, but the present invention is not limited to the following examples.
[0106] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0107] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0108] Example 1
[0109] 1) Preparation of shear thickening copolymer
[0110] (1) dissolving 0.05 mol of methacryloyl chloride and 0.05 mol of (2,4,4-trimethylpentan-2-yl)phenol polyoxyethylene ether (n=5, purchased from Chengdu Kelong Chemical Co., Ltd. OP-5) in dichloromethane, and reacting for 12 hours in an ice bath to obtain a monomer of octylphenol polyoxyethylene ether methacrylate (n=5);
[0111] (2) adding 70% acrylamide, 20% acrylic acid, 9% sorbic acid and 1% octylphenol polyoxyethylene ether methacrylate (n=5) in mole fraction to ethanol to prepare an ethanol solution with a monomer concentration of 10%, heating the solution to 60° C. and adding azobisisobutyronitrile as an initiator, reacting the solution for 7 hours, and removing the solvent to obtain a copolymer intermediate;
[0112] (3) 5 g of the copolymer intermediate was dissolved in 200 mL of dichloromethane, and 0.1 g of hexadecyltrimethylammonium bromide, 4.5 g of bromoform and 6 g of sodium hydroxide were added. Nitrogen was passed through for 1 hour, and then stirred at room temperature for 24 hours. The organic phase was washed with ethanol until neutral, and then dried and rotary evaporated to obtain a shear thickening copolymer.
[0113] Figure 1 This is the infrared spectrum of the shear thickening copolymer obtained in Example 1. It can be seen from the infrared spectrum that the synthesized shear thickening copolymer contains amide groups, carboxyl groups, ether bonds, benzene rings and brominated hydrocarbons, indicating that the synthesized polymer is a polymer with a structure shown in formula (1).
[0114] 2) Preparation of high temperature resistant fracturing fluid
[0115] Prepare a high temperature resistant fracturing fluid with a mass fraction of 0.3 wt % by slowly adding 0.3 parts by weight of a copolymer thickener to 99.7 parts by weight of water under stirring conditions, and stir for 2 hours to obtain a high temperature resistant fracturing fluid.
[0116] Use HAKKE RS600 rheometer and set the shear rate to 10-1000s -1 , shear time is 10min, and the viscosity of the fracturing fluid is observed to change with the shear rate. Figure 2 The variable shear rheological curve of the fracturing fluid prepared with 0.3 wt% of the copolymer in Example 1 at 160°C is shown in Figure 2 It can be seen that the high temperature resistant fracturing fluid prepared in this embodiment has a shear rate of more than 100s -1 Shear thickening phenomenon occurs.
[0117] Example 2
[0118] 1) Preparation of shear thickening copolymer
[0119] (1) dissolving 0.05 mol of methacryloyl chloride and 0.05 mol of (2,4,4-trimethylpentan-2-yl)phenol polyoxyethylene ether (n=7, purchased from Chengdu Kelong Chemical Co., Ltd. OP-7) in dichloromethane, and reacting for 12 hours in an ice bath to obtain a monomer of octylphenol polyoxyethylene ether methacrylate (n=7);
[0120] (2) adding 70% acrylamide, 20% acrylic acid, 8% sorbic acid and 2% octylphenol polyoxyethylene ether methacrylate (n=7) in mole fraction to ethanol to prepare an ethanol solution with a monomer concentration of 10%, heating the solution to 65° C. and adding azobisisobutyronitrile as an initiator, and performing a polymerization reaction for 7 hours to obtain a copolymer intermediate;
[0121] (3) 5 g of the copolymer intermediate was dissolved in 200 mL of dichloromethane, and 0.1 g of hexadecyltrimethylammonium bromide, 4.5 g of bromoform and 6 g of sodium hydroxide were added. Nitrogen was passed through for 1 hour, and then stirred at room temperature for 24 hours. The organic phase was washed with ethanol until neutral, and then dried and rotary evaporated to obtain a shear thickening copolymer.
[0122] 2) Preparation of high temperature fracturing fluid
[0123] Prepare a high temperature resistant fracturing fluid with a mass fraction of 0.3 wt %: slowly add 0.3 wt parts of copolymer thickener to 99.7 wt parts of water under stirring conditions, and stir for 2 hours to obtain a high temperature resistant fracturing fluid.
[0124] Use HAKKE RS600 rheometer and set the shear rate to 10-1000s -1 , shear time is 10min, and the viscosity of the fracturing fluid is observed to change with the shear rate. Figure 3 The shear recovery rheological curve of the fracturing fluid prepared with 0.3 wt% copolymer in Example 2 is shown in Figure 3It can be seen that the high temperature resistant fracturing fluid prepared in this embodiment has a 1000s -1 After cutting, in 100s -1 At a shear rate of , the viscosity is higher than the initial viscosity. Figure 4 The temperature and shear resistance rheological curve of the fracturing fluid prepared with 0.3 wt% of the copolymer in Example 3 is shown in Figure 4 It can be seen that the high temperature resistant fracturing fluid prepared in this embodiment has a high temperature resistance at 140°C and 100s -1 After 120 minutes of shearing, the viscosity remained above 100 mPa·s. When the temperature reached 140°C, the viscosity of the fracturing fluid became stable with the increase of time.
[0125] Example 3
[0126] 1) Preparation of shear thickening copolymer
[0127] (1) dissolving 0.05 mol of methacryloyl chloride and 0.05 mol of (2,4,4-trimethylpentan-2-yl)phenol polyoxyethylene ether (n=9, purchased from Chengdu Kelong Chemical Co., Ltd. OP-9) in dichloromethane, and reacting for 12 hours in an ice bath to obtain a monomer of octylphenol polyoxyethylene ether methacrylate (n=9);
[0128] (2) adding 72% acrylamide, 23% acrylic acid, 4% sorbic acid and 1% octylphenol polyoxyethylene ether methacrylate (n=9) in mole fraction to ethanol to prepare an ethanol solution with a monomer concentration of 8%, heating the solution to 65° C. and adding azobisisobutyramidine hydrochloride initiator, and performing polymerization reaction for 8 hours to obtain a copolymer intermediate;
[0129] (3) 5 g of the copolymer intermediate was dissolved in 200 mL of dichloromethane, and 0.08 g of hexadecyltrimethylammonium bromide, 4 g of bromoform and 5 g of sodium hydroxide were added. Nitrogen was passed through for 1 hour, and then stirred at room temperature for 24 hours. The organic phase was washed with ethanol until neutral, and then dried and rotary evaporated to obtain a shear thickening copolymer.
[0130] 2) Preparation of high temperature resistant fracturing fluid
[0131] Prepare a high temperature resistant fracturing fluid with a mass fraction of 0.4 wt % by slowly adding 0.4 parts by weight of a copolymer thickener to 99.6 parts by weight of water under stirring conditions, and stir for 2 hours to obtain a high temperature resistant fracturing fluid.
[0132] Use HAKKE RS600 rheometer and set the shear rate to 10-1000s -1 , shear time is 10min, and the viscosity of the fracturing fluid is observed to change with the shear rate. Figure 5The temperature and shear resistance rheological curve of the fracturing fluid prepared with 0.4 wt% of the copolymer in Example 3 is shown in Figure 5 It can be seen that the high temperature resistant fracturing fluid prepared in this embodiment has a high temperature resistance at 160°C and 100s -1 After 120 minutes of shearing, the viscosity remained above 80 mPa·s. When the temperature reached 160°C, the viscosity of the fracturing fluid increased slowly with time, and shear thickening occurred.
[0133] Example 4
[0134] 1) Preparation of shear thickening copolymer
[0135] (1) dissolving 0.05 mol of methacryloyl chloride and 0.05 mol of (2,4,4-trimethylpentan-2-yl)phenol polyoxyethylene ether (n=10, purchased from Chengdu Kelong Chemical Co., Ltd. OP-10) in dichloromethane, and reacting for 12 hours under ice bath conditions to obtain a monomer of octylphenol polyoxyethylene ether methacrylate (n=10);
[0136] (2) adding 70% acrylamide, 25% acrylic acid, 4.5% sorbic acid and 0.5% octylphenol polyoxyethylene ether methacrylate (n=10) in mole fraction to ethanol to prepare an ethanol solution with a monomer concentration of 8%, heating to 65° C. and adding azobisisobutyramidine hydrochloride initiator, and performing polymerization reaction for 8 hours to obtain a copolymer intermediate;
[0137] (3) 5 g of the copolymer intermediate was dissolved in 200 mL of dichloromethane, and 0.05 g of hexadecyltrimethylammonium bromide, 4 g of bromoform and 5 g of sodium hydroxide were added. Nitrogen was passed for 1 hour, and then stirred at room temperature for 24 hours. The organic phase was washed with ethanol until neutral, and then dried and rotary evaporated to obtain a shear thickening copolymer.
[0138] 2) Preparation of high temperature resistant fracturing fluid
[0139] Prepare a high temperature resistant fracturing fluid with a mass fraction of 0.5 wt % by slowly adding 0.5 parts by weight of a copolymer thickener to 99.5 parts by weight of water under stirring conditions, and stir for 2 hours to obtain a high temperature resistant fracturing fluid.
[0140] Use HAKKE RS600 rheometer and set the shear rate to 10-1000s -1 , shear time is 10min, and the viscosity of the fracturing fluid is observed to change with the shear rate. Figure 6 The temperature and shear resistance rheological curve of the fracturing fluid prepared with 0.5% by weight of the copolymer in Example 4 is shown in Figure 6 It can be seen that the high temperature resistant fracturing fluid prepared in this embodiment has a high temperature resistance at 180°C and 100s -1After 120 minutes of shearing, the viscosity remained above 100 mPa·s. When the temperature reached 180°C, the viscosity of the fracturing fluid increased slowly with time, and shear thickening occurred.
[0141] Example 5
[0142] 1) Preparation of shear thickening copolymer
[0143] (1) dissolving 0.05 mol of methacryloyl chloride and 0.05 mol of (2,4,4-trimethylpentan-2-yl)phenol polyoxyethylene ether (n=10, as above) in dichloromethane, and reacting for 12 hours in an ice bath to obtain a monomer of octylphenol polyoxyethylene ether methacrylate (n=10);
[0144] (2) adding 75% acrylamide, 15% acrylic acid, 9% sorbic acid and 1% octylphenol polyoxyethylene ether methacrylate (n=10) in mole fraction to ethanol to prepare an ethanol solution with a monomer concentration of 10%, heating to 70° C. and adding azobisisobutyramidine hydrochloride initiator, and performing polymerization reaction for 8 hours to obtain a copolymer intermediate;
[0145] (3) 5 g of the copolymer intermediate was dissolved in 200 mL of dichloromethane, and 0.1 g of hexadecyltrimethylammonium bromide, 5 g of bromoform and 8 g of sodium hydroxide were added. Nitrogen was passed for 1 hour, and then stirred at room temperature for 24 hours. The organic phase was washed with ethanol until neutral, and then dried and rotary evaporated to obtain a shear thickening copolymer.
[0146] 2) Preparation of high temperature resistant fracturing fluid
[0147] Prepare a high temperature resistant fracturing fluid with a mass fraction of 0.6 wt % by slowly adding 0.6 parts by weight of a copolymer thickener to 99.4 parts by weight of water under stirring conditions, and stir for 2 hours to obtain a high temperature resistant fracturing fluid.
[0148] Use HAKKE RS600 rheometer and set the shear rate to 10-1000s -1 , shear time is 10min, and the viscosity of the fracturing fluid is observed to change with the shear rate. Figure 7 The temperature and shear resistance rheological curve of the fracturing fluid prepared with 0.6 wt% of the copolymer in Example 5 is shown in Figure 7 It can be seen that the high temperature resistant fracturing fluid prepared in this embodiment has good thermal stability at 200°C and 100s -1 After 120 minutes of shearing, the viscosity remained above 100 mPa·s. When the temperature reached 200°C, the viscosity of the fracturing fluid increased slowly with time, and shear thickening occurred.
[0149] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A copolymer, characterized in that The copolymer has a structure represented by formula (1), In formula (1), R1 and R2 are each independently selected from halogen; R3 and R4 are each independently selected from H and an alkyl group having 1 to 6 carbon atoms; R5 is selected from an alkyl group having 1 to 20 carbon atoms; a, b, c and d represent the molar percentage of the structural unit, a is 55-75%, b is 15-25%, c is 1-10%, and d is 0.1-5%; n is an integer selected from 5-10.
2. The copolymer according to claim 1, wherein In formula (1), R1 and R2 are each independently selected from F, Cl, Br or I, preferably each independently selected from Cl or Br; R3 and R4 are each independently selected from H and an alkyl group having 1 to 3 carbon atoms, preferably each independently selected from H and a methyl group; R5 is selected from an alkyl group having 6 to 10 carbon atoms, preferably an octyl group; a, b, c and d represent the molar percentage of the structural unit, a is 70-75%, b is 15-25%, c is 4-9%, and d is 0.5-2%; n is selected from 5, 7, 9 or 10.
3. The copolymer according to claim 1, wherein The copolymer has a structure shown in formula (2), In formula (2), a, b, c and d represent the molar percentage of the structural unit, a is 55-75%, b is 15-25%, c is 1-10%, and d is 0.1-5%; n is an integer selected from 5-10.
4. The copolymer according to claim 3, wherein In formula (2), a, b, c and d represent the molar percentage of the structural unit, a is 70-75%, b is 15-25%, c is 4-9%, and d is 0.5-2%; n is selected from 5, 7, 9 or 10.
5. A method for preparing a copolymer, characterized in that: The Method The following steps are included: 1) in the presence of an initiator, subjecting a monomer solution containing monomer A, monomer B, monomer C and monomer D to a polymerization reaction to obtain a polymer intermediate; 2) a step of subjecting the polymer intermediate to a halogenation reaction with a halogenating agent, Wherein, the monomer A is acrylamide and / or alkyl acrylamide, the monomer B is acrylic acid and / or alkyl acrylic acid, the monomer C is sorbic acid, methyl sorbate or ethyl sorbate, and the monomer D is alkylphenol polyoxyethylene ether methacrylate; The alkyl groups in the alkyl acrylamide and the alkyl acrylic acid are independently selected from H and alkyl groups with 1 to 6 carbon atoms; the alkyl group in the alkylphenol polyoxyethylene ether methacrylate is selected from alkyl groups with 1 to 20 carbon atoms; Based on the total molar amount of monomer A, monomer B, monomer C and monomer D, the monomer A is 55-75 mol%, the monomer B is 15-25 mol%, the monomer C is 1-10 mol%, and the monomer D is 0.1-5 mol%.
6. The method according to claim 5, wherein: The alkyl groups in the alkyl acrylamide and the alkyl acrylic acid are each independently selected from H and an alkyl group having 1 to 3 carbon atoms, preferably H and methyl; Preferably, the alkyl group in the alkylphenol polyoxyethylene ether methacrylate is selected from alkyl groups having 6 to 10 carbon atoms, preferably octyl.
7. The method according to claim 5, wherein: Based on the total molar amount of monomer A, monomer B, monomer C and monomer D, the monomer A is 70-75 mol%, the monomer B is 15-25 mol%, the monomer C is 4-9 mol%, and the monomer D is 0.5-2 mol%.
8. The method according to any one of claims 5 to 7, wherein: The monomer A is one or more of acrylamide, methacrylamide, ethyl acrylamide and propyl acrylamide; Preferably, the monomer B is one or more of acrylic acid, methacrylic acid, ethacrylic acid and propylacrylic acid; Preferably, the monomer D is selected from one or more of the compounds wherein n=5, n=7, n=9 and n=10 in the following formula (3), 9. The method according to any one of claims 5 to 7, wherein: The initiator is one or more of azobisisobutyronitrile, azobisisovaleronitrile and azobisisobutyramidine hydrochloride; Preferably, the amount of the initiator is 0.05-0.2% of the total weight of the monomers.
10. The method according to any one of claims 5 to 7, wherein: The solvent in the monomer solution is one or more of methanol, ethanol, ether, acetone, toluene and xylene, preferably one or more of ethanol, ether and acetone.
11. The method according to any one of claims 5 to 7, wherein: The polymerization reaction conditions include: polymerization temperature of 60-70° C., and polymerization time of 7-8 hours.
12. The method according to any one of claims 5 to 7, wherein: In step 2), the halogenating agent is bromoform; Preferably, the amount of the halogenating agent used is 3-8% by weight of the polymer intermediate.
13. The method according to any one of claims 5 to 7, wherein: The conditions of the halogenation reaction include: reaction temperature of 5-45° C., and reaction time of 10-80 hours.
14. A fracturing fluid, characterized in that: The fracturing fluid contains the copolymer according to any one of claims 1 to 4.
15. The fracturing fluid according to claim 14, wherein: The content of the copolymer in the fracturing fluid is 0.1-1% by weight.
Citation Information
Patent Citations
Use of anionically and cationically ampholytic copolymers
CN101227887A
Copolymer as well as preparation method and application of copolymer
CN104418969A
Acrylamide copolymer, as well as preparation method and application thereof
CN104628942A
Polymer thickening agent, preparation method thereof and gel fracturing fluid
CN113980172A
Unsaturated carboxylic acid-based copolymer and method for producing the same
JP2002012628A
Cited By
Multi-copolymer and preparation method and application thereof
CN122277805A